2020
DOI: 10.1017/jfm.2020.716
|View full text |Cite
|
Sign up to set email alerts
|

Dissipation element analysis of non-premixed jet flames

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 49 publications
0
4
0
Order By: Relevance
“…2017; Denker et al. 2020; Gauding et al. 2021), have recently gained relevance for mixing and combustion models, this result has a direct application.…”
Section: Summary and Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…2017; Denker et al. 2020; Gauding et al. 2021), have recently gained relevance for mixing and combustion models, this result has a direct application.…”
Section: Summary and Discussionmentioning
confidence: 97%
“…By analysing structure functions across the jet, we demonstrated that higher-order statistics conditioned on fully turbulent regions inside the turbulent envelope are largely independent of external intermittency and recover self-similarity at small and intermediate scales. As zonal models, for example based on gradient trajectories (Mellado et al 2009;Gauding et al 2017;Denker et al 2020;Gauding et al 2021), have recently gained relevance for mixing and combustion models, this result has a direct application. Furthermore, it is necessary to examine how the conditional structure functions S n,tt depend on the threshold of the enstrophy that determines the position of the IB.…”
Section: Summary and Discussionmentioning
confidence: 99%
“…A temporally evolving turbulent jet set-up is known to be a good compromise between our ability to use accurate numerical methods, the computational efforts for sufficiently large Reynolds number and capturing the physics of turbulent jets (e.g. da Silva & Pereira 2008;van Reeuwijk & Holzner 2013;Krug et al 2017;Cimarelli et al 2020;Denker et al 2020). Therefore, the combination of newly derived similarity solutions and DNS of temporal jets seems to represent a useful combination of tools for the analysis of the important features of turbulent jet flows.…”
Section: Introductionmentioning
confidence: 99%
“…2020; Denker et al. 2020). Therefore, the combination of newly derived similarity solutions and DNS of temporal jets seems to represent a useful combination of tools for the analysis of the important features of turbulent jet flows.…”
Section: Introductionmentioning
confidence: 99%